Spot diagnosis: An ominous rash in a newborn - Wong William; So King-Woon; Hon Kam-Lun; Cheung Kam-Lau (BMC, 2009)
Abstract Purpura fulminans (PF) is an ominous cutaneous condition usually associated with meningococcemia. PF in the newborn is rarely reported. We report the case of a female preterm infant with extensive PF due to group B streptococcus (GBS) septicemia. She developed multi-organ system failure despite neonatal intensive care support and succumbed 9 days later. GBS, sensitive to penicillin, was isolated from the blood cultures of the mother and the infant. Invasive early GBS infection is common in the newborn and is empirically treated with prompt institution of intravenous antibiotics. PF associated with GBS is a rare cutaneous sign that must not be missed. Mortality remains high despite aggressive treatment and ICU support.